Factors Influencing the Performance of PT Pos Indonesia (Persero) Jember Main Branch Office with Logistics Innovation as an Intervening Variable - Widodo, Erlangga Putragung; Waskito, Saptono Kusdanu; Lestiani, Melia Eka (Semarak International Journal of Transportation and Logistics, 2025)
The revenue of the Courier and Logistics Business in the Retail Segment at PT Pos Indonesia, Jember Main Branch, in 2024 reached IDR 6,796,868,820, falling short of the target of IDR 8,109,800,000. This discrepancy indicates performance issues within PT Pos Indonesia, Jember Main Branch. This study aims to examine the factors influencing company performance, including Disruptive Environment, Logistics Agility, and Ambidextrous Leadership, with Logistics Innovation as an intervening variable. The study population consists of 229 employers, with a sample size of 146 respondents determined using Slovin’s formula. All indicators have values ranging from 0.710 to 0.931, exceeding the threshold of 0.7, confirming their validity. Furthermore, all dimensions have Cronbach’s Alpha values above 0.7, indicating reliability. The results show a positive and significant effect of the Disruptive Environment on Logistics Innovation, with a T-Statistic of 3.384 and a p-value of 0.047. Similarly, Logistics Agility has a positive and significant effect on Logistics Innovation, with a T-Statistic of 2.006 (>1.96) and a p-value of 0.045. Ambidextrous Leadership also exhibits a positive and significant effect on Logistics Innovation, with a T-Statistic of 1.992 (>1.96) and a p-value of 0.045. Moreover, Disruptive Environment, Logistics Agility, and Ambidextrous Leadership collectively have a positive and significant impact on Logistics Innovation, as indicated by an R-Square value of 0.579. Additionally, Logistics Innovation has a positive and significant effect on the performance of PT Pos Indonesia, Jember Main Branch, with a T-Statistic of 16.450 and a p-value of 0.000. To enhance revenue, PT Pos Indonesia, Jember Main Branch, should continuously implement innovations, particularly in optimizing the distribution process to deliver goods to customers more efficiently than its competitors.